Just Open Your Mind? A Randomized, Controlled Study on the Effects of Meditation on Creativity - Bashmakova, Iana; Shcherbakova, Olga (Frontiers in Psychology, 2021)
Creativity is a crucial prerequisite for innovation, successful problem-solving, and self-expression; but how do we affect creative thinking in a positive way? Present study investigated the effects of Open Monitoring meditation (OMM) on creativity. We proposed that OMM will benefit creativity in metaphor production by cognitive flexibility (CF) enhancement. In the main study, participants were randomly assigned to one of the three groups: meditation, active and passive control. The first two groups performed an audio-guided task (real meditation or a narrative on house plants) for two weeks, and the third one had no task. Pre- and post-tests included measures of metaphor production, CF, state, sustained attention, attention shifting, intelligence. We found no significant itra- or intergroup differences that would suggest OMM effects on creativity. Further, no links were found between measures of metaphor creativity and CF. Findings reveal potential challenges of using meditation as a cognitive enhancement tool. Methodological issues concerning meditation research, as well as creativity and CF measures, are discussed.